REPRESENTASI NILAI BUDAYA ACEH PADA FILM HIKAYAT TERAKHIR - Inayatillah, Inayatillah; Junaidi, Junaidi; Mariani, Mariani (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2022)
Film is one of the effective and popular media in presenting the cultural values ​​and life of a region or nation. The film that is used as the object of this research is the film "Hikayat Terakhir". This film is an interesting study material because it explains about the saga culture that exists in Aceh. The purpose of this research is to find out the representation of Acehnese cultural values ​​which is shown in the film Hikayat Terakhir. This study uses a descriptive qualitative approach. The data analysis technique used in this research is semiotic analysis using the Charles Sanders Pierce approach. The results of the study show that in this film there is a lot of data showing the cultural values ​​of Aceh which are depicted through the film's scenes and dialogues. Acehnese cultural values ​​which are shown through the signs depicted in the film include the use of language, attitude of responsibility, kinship, clothing, traditional houses, traditions, values ​​of manners, and religious values. These cultural values ​​can be seen in the data findings that have been described in this study